Randomised controlled study of two counselling models at the Swedish alcohol helpline: Effectiveness and sustainability outcomes at 12-month follow-up. Issue 2 (April 2022) - Nguyen, Thi-Thuy-Dung; Säfsten, Eleonor; Andersson, Filip; Galanti, Maria Rosaria
Aim: This two-arm parallel randomised controlled trial explored the effectiveness of a brief counselling model compared with the usual multi-session counselling at an alcohol telephone helpline.Methods: A total of 320 callers who contacted the Swedish Alcohol Helpline (SAH) because of hazardous or harmful alcohol use were randomised to either brief structured intervention (self-help booklet plus one proactive call) or usual care (multi-session telephone counselling). The primary outcome was a downward shift in risk level at 12-month follow-up compared with baseline, based on self-reports. Sustained risk level reduction throughout the whole follow-up was also assessed as secondary outcome.Results: Both interventions were significantly associated with a shift to a lower level of risky alcohol use (75% among participants in the brief structured intervention, and 70% in the usual care group) after 12 months. There was no difference between the two interventions in the proportions changing alcohol use or sustaining risk level reduction.Conclusion: In the context of telephone helplines, minimal and extended interventions appear to be equally effective in promoting long-term change in alcohol use.